Observations anatomiques concernant la valve atrioventricuiaire gauche humaine - Soares, J. C.; Ferreira, A. L. (My University, 1985)
30 hearts of male and female, white and non-white Brazilians of different ages were studied. The leaflets of the left atrioventricular valves were removed near the fibrous ring and anatomically studied under chirurgical microscope. The authors observed: the leaflet's shape, the presence of commissures, the implantation manner of the chordae tendineae and the distribution on the leaflets. Special attention was concentrated on the terminology used by different authors for the structures of the 'mitral complex'.
Anatomical observations on the left human atrioventricular valve
Keywords: heart; human; mitral valve; normal human; Adult; Brazil; Chordae Tendineae; English Abstract; Female; Human; Male; Mitral Valve; Support, Non-U.S. Gov't; Terminology